(untitled) (Asian Journal of Medical and Biological Research, 2015)
An investigation was conducted to determine the seroprevalence of brucellosis in pet dogs of Dhaka City Corporation area. A total of 50 sera samples from pet dogs were collected. Additional data on risk factors (breed, age, sex, any abnormality during sample collection etc.) were recorded during sample collection by using standard questionnaire. Sera were separated from blood samples and tested with the Rose Bengal Plate Test (RBPT) and Indirect Enzyme linked Immunosorbent Assay (IELISA) parallely. The overall seroprevalence of brucellosis in pet dogs was found 4.00% by RBPT & IELISA. The results of both serological methods were equal in terms of ability to detect Canine Brucellosis. Statistically higher seroprevalence of brucellosis (6.06%) was found in dog aged 1.5 to 2.5 years. Higher seroprevalence (15.38%) was found also in female pet dogs and no response in male pet dogs. Asian J. Med. Biol. Res. June 2015, 1(1): 17-21